2016
DOI: 10.1002/ejic.201600163
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Chemistry of an Unsymmetrical Naphthyridine‐Based Tetradentate Ligand toward Various Transition‐Metal Ions

Abstract: An unsymmetrical ligand, 2‐(2‐pyridinyl)‐7‐(pyrazol‐1‐yl)‐1,8‐naphthyridine (L5) was prepared for the construction of a series of dinuclear complexes. Treatment of L5 with [Ru2(µ‐OAc)4Cl] followed by anion metathesis afforded [(L5)(µ‐OAc)3Ru2](PF6) (3). Reaction of L5 with 2 equiv. of Ni(OAc)2 provided [Ni4(L5)2(µ‐OH)4(CF3COO)2](CF3COO)2 (5). Reaction of [Re2(CO)8(CH3CN)2] with L5 in a refluxing chlorobenzene solution gave a mixture of dirhenium (6) and monorhenium (7) complexes. The monocobalt complex 8 was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Studies on bimetallic complexes in this laboratory have focused on binucleating ligands with the 1,8-naphthyridine backbone. The naphthyridine backbone can be symmetrically , or unsymmetrically functionalized with side arms at the 2- and 7- positions to provide a rigid pocket for two transition metals, and these side arms can be the same, as in the DPEN and DPFN ligands, or different, as in the DPEPN ligand (Figure ). Previous studies from our laboratory demonstrated that the DPEN and DPFN ligands readily afford dicopper­(I) complexes in which bridging ligands bind symmetrically between the two Cu­(I) centers, and a dicopper DPFN-alkynyl complex was shown to be a competent catalyst for the copper-catalyzed azide–alkyne cycloaddition (CuAAC) reaction. ,, Such dicopper-alkynyl species are proposed intermediates in several catalytic processes, including the Glaser–Hay coupling and the CuAAC reaction, , where their role has been studied computationally. …”
Section: Introductionmentioning
confidence: 78%
“…Studies on bimetallic complexes in this laboratory have focused on binucleating ligands with the 1,8-naphthyridine backbone. The naphthyridine backbone can be symmetrically , or unsymmetrically functionalized with side arms at the 2- and 7- positions to provide a rigid pocket for two transition metals, and these side arms can be the same, as in the DPEN and DPFN ligands, or different, as in the DPEPN ligand (Figure ). Previous studies from our laboratory demonstrated that the DPEN and DPFN ligands readily afford dicopper­(I) complexes in which bridging ligands bind symmetrically between the two Cu­(I) centers, and a dicopper DPFN-alkynyl complex was shown to be a competent catalyst for the copper-catalyzed azide–alkyne cycloaddition (CuAAC) reaction. ,, Such dicopper-alkynyl species are proposed intermediates in several catalytic processes, including the Glaser–Hay coupling and the CuAAC reaction, , where their role has been studied computationally. …”
Section: Introductionmentioning
confidence: 78%
“…Indeed, upon treatment with mixtures of different metals, symmetrical ligands are expected to yield a mixture of products rather than one well‐defined heterobimetallic complex . The few reported unsymmetrical naphthyridine‐based dinucleating ligands are associated with low‐yielding syntheses, similar coordination environments, and formation of homometallic complexes upon metalation …”
Section: Methodsmentioning
confidence: 99%
“…[23][24][25] Moreover,n aphthyridine-based bimetallicc omplexes have been shown to catalyzearange of reactions. [33] Here we report the selective synthesis of an isostructural series of heterobimetallic complexes that employs an unsymmetricaln aphthyridine-based ligand (Scheme 1). Indeed, upon treatment with mixtures of differentm etals, symmetrical ligandsa re expected to yield am ixture of products rather than one well-defined heterobimetallic complex.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are a growing number of situations documented where this approach does not produce bimetallic products. [8][9][10][11][12][13] There are several alternative approaches, none of which are widely generalisable. Use of preformed bimetallic precursors is an established method, but is limited to precursors containing metal-metal bonds.…”
Section: Introductionmentioning
confidence: 99%